Pengaruh Promosi Digital dan Brand Image terhadap Niat Beli di Tan-Panama Coffee di Kota Denpasar - Ni Made Pramesi Dwi Winanda; Ni Made Wahyuni; Ida Ayu Putu Santi Purnamawati (LPPM Universitas Bina Sarana Informatika, 2026)
The purpose of this paper is to contribute to the management literature in the creative culinary coffee shop industry by examining the influence of digital promotion and brand image on simultaneous and partial purchase intention. Using a descriptive research approach, this study uses quantitative data to assess how purchase intention is influenced by digital promotion and brand image. The research location is Tan-Panama coffee shop, Denpasar. The research sample includes 102 consumers who have made purchases. Data collection was conducted using a questionnaire survey method with a simple random sampling technique. The data analysis technique used SPSS 26.0 software. The results of the study indicate that digital promotion and brand image together have a significant positive influence on purchase intention. Then, digital promotion has a positive and significant impact on purchase intention among consumers. Furthermore, brand image greatly influences purchase intention. Practically, this study will help management or marketers to understand the power of digital promotion as a marketing tool and brand image more strategically to attract new customers. Understanding how it affects consumer purchase intention is very important and has strong implications for marketers. The implication of this study is that the management of Tan-Panama coffee shop must build digital promotions and strengthen its brand image so that it can increase purchase intention.